Análise da temperatura de superfície em ambientes urbanos: um estudo por meio de sensoriamento remoto no município de Goiânia, Goiás (2002 – 2011) - Silvio Braz de Sousa; Laerte Guimarães Ferreira (Confins)
Among the urban environmental impacts that need to be considered in the process of land use, is the change in the thermal field induced by the replacement of the natural land cover, followed by the appropriation of these spaces for anthropic activities. Within this scope, the present work, conducted in the city of Goiânia, capital of the state of Goiás, aims to analyze the spatial distribution and patterns of land surface temperatures (LST) for the years 2002 and 2011, using data from the TM and ETM+ sensors (Landsat series). The method used to estimate the LST was evaluated and validated through comparisons between the thermal image, produced using the ETM+ band, and the MOD11A1 product, which presented good correlation (r² of 0.70). A preliminary comparative analysis, based on the thermal anomaly images, indicated that August 2011, in spite of milder temperatures on day 15, was potentially hotter, particularly along the urbanized areas, in relation to 2002.